2015
DOI: 10.1371/journal.pone.0117459
|View full text |Cite
|
Sign up to set email alerts
|

A Fatal Combination: A Thymidylate Synthase Inhibitor with DNA Damaging Activity

Abstract: 2′-deoxy-5-ethynyluridine (EdU) has been previously shown to be a cell poison whose toxicity depends on the particular cell line. The reason is not known. Our data indicates that different efficiency of EdU incorporation plays an important role. The EdU-mediated toxicity was elevated by the inhibition of 2′-deoxythymidine 5′-monophosphate synthesis. EdU incorporation resulted in abnormalities of the cell cycle including the slowdown of the S phase and a decrease in DNA synthesis. The slowdown but not the cessa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 35 publications
2
50
0
Order By: Relevance
“…The inhibitory activity exhibited by EdU against HEK293 cells and T. cruzi has been similarly shown for a number of cell lines both in vivo and in vitro [30,31]. For example, it has been demonstrated that following 72 hours exposure of HEK293 cells to EdU there was cytotoxicity displayed, with an IC 50 value of 0.060 ± 0.043 μM identified [32].…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…The inhibitory activity exhibited by EdU against HEK293 cells and T. cruzi has been similarly shown for a number of cell lines both in vivo and in vitro [30,31]. For example, it has been demonstrated that following 72 hours exposure of HEK293 cells to EdU there was cytotoxicity displayed, with an IC 50 value of 0.060 ± 0.043 μM identified [32].…”
Section: Discussionmentioning
confidence: 79%
“…Some strains used by Sánchez-Valdéz et al were transfected with pTREX-Luciferase/ TdTomato and it would be of benefit to compare with wild type parasites. The impact of EdU causing time dependant inhibition of cell growth on various mammalian cell lines is well documented [52,53]. In the studies herein, exposure of EdU was limited to 2 or 4 hours incubation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To explore whether similar effects were encountered with another nucleoside analog, we treated the five different cell lines with 5-ethynyl-2′-deoxyuridine (5-EdU). While 5-EdU is generally recognized by the replication complex to promote DNA damage and cytotoxicity in dividing cells (Ligasová et al, 2015), its nucleotide counterpart does not serve as an efficient substrate for telomerase-mediated extension (Figure 1). Indeed, administration of 5-EdU induced cell death in all treated cells, regardless of their telomerase status (Figure 2C).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the depletion of dTMP and subsequently dTTP induced perturbations in the levels of the other deoxynucleotides (dATP, dGTP, and dCTP), resulting in a reduction of the DNA synthesis and repair [39]. These effects suggest that a combinatorial strategy with our complexes and traditional TS inhibitors, such as 5-fluorouracil, raltitrexed or pemetrexed might have great potential in killing cells even with innated or more elevated TS levels that are more elevated [40].…”
Section: Discussionmentioning
confidence: 99%